2019
DOI: 10.11648/j.ajns.20190804.20
|View full text |Cite
|
Sign up to set email alerts
|

Educational Intervention on Knowledge and Attitude Regarding Breast Cancer Self Examination

Abstract: The aim of the study is to assess the effect of the educational intervention regarding breast cancer among high school students. A quasi-experimental pre and posttest design were utilized to fulfill the aim of this study. This study was conducted in the classrooms of the selected female high private and governmental schools. Riyadh, Kingdome of Saudi Arabia. The school was selected by simple random sampling technique and sampling units were selected consecutively. The study was conducted on 400 high school fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The comparison of the mean differences between the pre-post-test scores for the intervention and control groups showed a statistically significant difference for knowledge of cervical cancer (t = 6.22, df = 780, p = 0.001). The result of the current research also congruent with Said et al (12) who showed that, there was a highly statistical significant improvement regarding cervical cancer knowledge concerning meaning, types, risks, symptoms, diagnostic and treatment P ≤ 0.001. As well as, the findings agreed with Naregal et al (23) who revealed that there was a significant difference between the two tests was tested using paired t-test the level of significant was highly (p<0.001) indicated that there was a significant difference in the knowledge of women on cervical cancer.…”
Section: Zagazig Nursing Journalsupporting
confidence: 91%
See 1 more Smart Citation
“…The comparison of the mean differences between the pre-post-test scores for the intervention and control groups showed a statistically significant difference for knowledge of cervical cancer (t = 6.22, df = 780, p = 0.001). The result of the current research also congruent with Said et al (12) who showed that, there was a highly statistical significant improvement regarding cervical cancer knowledge concerning meaning, types, risks, symptoms, diagnostic and treatment P ≤ 0.001. As well as, the findings agreed with Naregal et al (23) who revealed that there was a significant difference between the two tests was tested using paired t-test the level of significant was highly (p<0.001) indicated that there was a significant difference in the knowledge of women on cervical cancer.…”
Section: Zagazig Nursing Journalsupporting
confidence: 91%
“…According to current statistics, 299 women die from cervical cancer each year while 514 people are diagnosed with this disease. (12) Patients with cervical cancer have more physical and psychological suffering due to cancer discomfort, which often interferes with their quality of life. A study has shown that the incidence of cancer-related fatigue in patients with gynecological malignant tumors is about 93%.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Assessment phase: in this phase, the researcher conducted the study tool (pre-test) for participants about knowledge and attitudes related to cervical cancer and screening. The interview took [25][26][27][28][29][30][31][32][33][34][35] Table (1) shows that 47 % of the participants were women aged 30-<40. Also, 36 % and 28 % have Secondary or University education.67 % of the participant women have sufficient income.57 % of the participant women are a housewife, and 51 % of the total live in urban places Table 2 presents that 91 % of the participant women haven't family history of cervical cancer, 67% have -3 < 5 days of menstruation and 58 % of the participant women have moderate amount of blood during menstruation.…”
Section: Data Was Collected Through the Following Phasesmentioning
confidence: 99%